Adolescent Knowledge Indexes in Detektif Indigo (Malay Literature, 2013)
Teenagers or adolescents today are more exposed to a variety of reading materials, whether produced by local or international publishers. Most of the novels revolve around the story of young love, friendship, family, school and natural life. Novels with a detective or investigation theme are also being produced to court young readers. The latter type of novels not only have their charm, but are also said to be able to hone young minds to think in-depth about current and global issues. Detektif Indigo (Indigo Detectives) is a novel in a series of detective novels written by Faisal Tehrani. It is about a group of youths calling themselves Detektif Indigo. The analysis will be using Peirce's Theory of Semiotics (1965) focusing on knowledge indexes regarding Islam, international relations, social relations and science in the novel. There are many aspects of knowledge that can be extracted from this work in order to shape young minds.Keywords: Detektif Indigo, hero, heroism, heroic deeds, heroic age, Ethnocentrism